Design and development of iAQSA as an innovative web application to support qualitative research - Majzob AbdelMaged, Amnah Salah; Hassan Rifat, Emon; Salleh, Norsaremah; Sheikh Ahmad, Ismail; Nordin, Mohd Shukri; Nik Abdullah, Nik Md. Saiful Azizi; Shamsuddin, Aizat (Akademia Baru Publishing (M) Sdn Bhd, 2024)
This paper presents a design and development of a web-based application called iAQSA that can assist and guide novice researchers to embark on a qualitative research method through fundamental stages. The web application serves as a platform in guiding the researchers from the beginning of the proposal to the reporting stage of the research findings. Additionally, it facilitates effective communication and collaboration between researchers and their supervisors. Supervisor can provide feedback, and approve submitted research proposals directly within the platform, enhancing the mentoring process and ensuring the quality of research outputs. iAQSA also provides a functionality to search for Islamic resources (from Al-Quran, Hadiths, and Islamic scholars) to support the research findings. The methodology used for the design and development of iAQSA was Agile Scrum, allowing for continuous feedback and improvements based on user input. Overall, iAQSA aims to streamline the qualitative research process, making it more efficient and manageable for postgraduate students. By providing a structured platform, it helps reduce the complexity and challenges associated with qualitative research process.